REMITTANCE INFLOWS AND EXCHANGE RATE IN KENYA: AN EMPRIRICAL INVESTIGATION - Mercy T. Musakwa; Nicholas. M Odhiambo (Acta Economica)
Purpose: This study investigated the impact of remittances on the nominal exchange rate in Kenya, using annual data from 1980 to 2020. The study was motivated by the need to find out how remittances affect the exchange rate in Kenya based on an increase in remittance inflows in low- and middle-income countries, including Kenya. This is important as Kenya continues to build a stable macroeconomic environment that supports economic growth and other milestones specified in the Sustainable Development Goals. Methodology: The study used the autoregressive distributed lag approach to examine this linkage. Results: The study, therefore, concludes that remittance inflows in Kenya are not associated with the appreciation of the currency, as predicted by some previous studies. Conclusion: The study, therefore, concludes that remittance inflows in Kenya are not associated with the Dutch-disease phenomenon. Recommendation: It is recommended that Kenya may continue to implement policies that support remittance inflows to realize an improvement in the balance of payments in the country.